[Rezension von: Divine evil?] - Gould, Graham (The journal of theological studies, 2011)
This collection of essays exemplifies the increasingly specific and sophisticated nature of the debates now taking place among philosophers of religion, whether Christians, followers of other faiths, or of none, who are prepared, to an extent that was not so often the case only a few years ago, to engage not only with general philosophical arguments about God but with specific doctrines, canonical literature, and theological traditions., Three essays, by Louise Antony, Edwin Curley, and Evan Fales, present the case against the moral character of the God revealed in Scripture.